Influência dos fenômenos El Niño e La Niña nos Padrões de distribuição da Precipitação no Estado do Pará - LEITE, Aquino de Jesus Melo (2019)
The present work is a study of the ocean ifluencia atmospheric phenomena in precipitation patterns of the Amazon , with the specific focus of analysis, three cities in the state of Pará ( Belém , Conceição do Araguaia and Obidos ) . In which belonging to the National Institute of Meteorology ( INMET ) , by conventional stations for the period from January 1975 to December 2000 . Still are used monthly data of sea surface temperature - SST and longwave radiation - ROL , according to the periods of El Niño events ( 1983) and La Niña (1985 ) , both belonging to data from the National Oceanic and Atmospheric Administration ( NOAA ) . To treat the rainfall data of the selected cities , we used Excel software , using your spreadsheet , Grads used the software for preparation of the figures of SST and OLR , and used the Rainfall Anomaly Index ( TCI) , to observe and analyze the wet and dry extremes in the study region . The results showed values of SST and OLR anomalously high in El Niño and La Niña , rainfall values of the cities above average in extreme rainy ee below average in dry extremes , and the extremes were striking behavior in almost all months study. The study concludes that the influence of atmospheric phenomena in the ocean rainfall in the Amazon are directly visible , and such a study is of great importance such that the most striking feature of Amazon is its quantitative rain , so the higher the number of studies being seriously , the better the developments in the understanding of many climate problems.